Design of an improvement plan applying the 5's methodology in the chicken roastery "El Pechugón". - Bolaños Jijón, Alexis Fernando; Mite Bastidas, Mariam Milena (Ingeniería Química y Desarrollo, 2024)
The objective of this research work is to design an improvement plan based on the 5'S methodology in the chicken roaster "El pechugón" with the purpose of increasing efficiency in business performance. To know the current situation of the business, a check list was used based on each of the phases of the 5'S methodology, in which deficits were determined such as: non-standard processes, lack of discipline, lack of cleaning protocol, poorly committed collaborators. , producing low-quality products and harming customer satisfaction. Faced with these deficits, action plans and a process manual were developed in order to provide the business with effective work spaces, reduce unproductive time, increase commitment and discipline in collaborators in order to improve the work environment together with the quality of the product and increase customer satisfaction.
Keywords: improvement plan; standardization; 5'S methodology; efficiency; productivity